2021
DOI: 10.21037/tcr-21-1276
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes involved in tamoxifen-resistant breast cancer using bioinformatics analysis

Abstract: Background The purpose of the present study was to investigate the molecular mechanisms of tamoxifen resistance in breast cancer and to identify potential targets for antitamoxifen resistance. Methods Differentially expressed genes (DEGs) in tamoxifen-resistant and tamoxifen-sensitive breast cancer cells were assessed using the GSE67916 dataset acquired from the Gene Expression Omnibus database. Gene ontology (GO) and pathway enrichment analyses were applied to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Using bioinformatic analysis Xiaopeng Wang et al discovered genes that had different expressions between tamoxifen-prone and tamoxifenresistant samples. Their results demonstrated an upregulation in NEAT1 as one of the differentially expressed genes (DEG) (105). Our ndings align with previous research and show an upregulation in the expression of NEAT1 in relation to breast cancer and tamoxifen resistance, and some of its targets include miR-548, miR-129-5p, and miR-218.…”
Section: Discussionsupporting
confidence: 91%
“…Using bioinformatic analysis Xiaopeng Wang et al discovered genes that had different expressions between tamoxifen-prone and tamoxifenresistant samples. Their results demonstrated an upregulation in NEAT1 as one of the differentially expressed genes (DEG) (105). Our ndings align with previous research and show an upregulation in the expression of NEAT1 in relation to breast cancer and tamoxifen resistance, and some of its targets include miR-548, miR-129-5p, and miR-218.…”
Section: Discussionsupporting
confidence: 91%
“…Although the YPEL proteins are reported to participate in cellular events, including proliferation, mitochondrial function, morphology, motility, differentiation, senescence, and death (Aerts et al, 2006b ; Baek et al, 2021 ; Baker, 2003 ; Blanco‐Sanchez et al, 2020 ; Dean et al, 2022 ; Farlie et al, 2001 ; Garcıá et al, 2019 ; Hosono et al, 2010 ; Jun et al, 2007 ; K. D. Kelley et al, 2010 ; J. H. Kim et al, 2020 ; Kong et al, 2018 ; J. Y. Lee et al, 2017 ; W. Li et al, 2022 ; Liang et al, 2010 ; Mattebo et al, 2021 ; Oki et al, 2016 ; Tan et al, 2015 ; Tuttle et al, 2012 ; J. Zhang et al, 2016 ) studies on YPEL2 are limited. Deregulated expression of YPEL2 is reported in various pathologies, including ccRCC (L. Wang et al, 2022 ), breast cancer (K. D. Kelley et al, 2010 ; Mascia et al, 2022 ; X. Wang & Wang, 2021 ), chronic idiopathic urticaria, and active hives (Lin et al, 2017 ). Using publically available pan‐cancer databases, for example, it was reported that YPEL2 , along with YPEL1 and YPEL5 , is differentially expressed in ccRCC and that increased expressions of YPEL1 , YPEL2 , and YPEL5 were associated with improved overall as well as disease‐specific survival of ccRCC patients (L. Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…TAM is one of the most chemotherapeutic medications used to treat breast cancer, however with time, cancer cells become resistant to TAM 8 11 . Some genes have been found to be associated with mechanisms of tamoxifen resistance 39 . Thus, exploration of more effective strategies is demanded to overcome resistance in breast cancer cells, improve TAM efficacy, and decrease undesirable side effects 9 , 38 40 .…”
Section: Discussionmentioning
confidence: 99%